E-SCAVENGER: UI/UX DESIGN OF AN ANDROID-BASED SCAVENGER APPLICATION USING HUMAN-CENTERED DESIGN METHODOLOGY IN PALOPO CITY - Ardiansyah Saputra; Nirsal, Nirsal (Jurnal Teknik Informatika (Jutif), 2024)
Efficient waste management and active community participation are key to keeping cities clean and reducing negative impacts on health and the environment. "E-Scavenger" is an innovative scavenger application implemented in Palopo City to increase waste collection efficiency and community involvement. This research involves a cross-sectional descriptive approach with data collection through direct observation and interviews. Additionally, Human Centered Design (HCD) research methods were applied to ensure the application was designed according to user needs and preferences, involving an iterative process centered on waste pickers and communities. “E-Scavenger” not only focuses on waste management, but also encourages active community participation in sustainable waste management efforts. The app provides real-time information about the location and type of waste that needs to be picked up, allowing waste pickers to work more efficiently. Additionally, “E-Scavenger” is designed to provide incentives to scavengers through a reward program and transparent reporting. The results of this research provide a comprehensive picture of the number of workers involved in waste management, the facilities and infrastructure available, as well as the volume of waste produced in Palopo City. With the implementation of "E-Scavenger", it is hoped that there will be a significant increase in waste collection efficiency and community participation, making Palopo City an example in technology-based waste management. It is hoped that the success of this innovation will make a positive contribution to public health and environmental sustainability in Palopo City.